2016
DOI: 10.1002/jbm.a.35961
|View full text |Cite
|
Sign up to set email alerts
|

Novel functionalization strategies of polymeric nanoparticles as carriers for brain medications

Abstract: For targeted brain delivery, nanoparticles (NPs) should bypass the blood-brain barrier (BBB). Novel functionalization strategies, based on low-density lipoprotein receptor (LDLR) binding domain, have been here tested to increase the brain targeting efficacy of poly d,l-lactic-co-glycolic acid (PLGA) NPs, biodegradable and suited for biomedical applications. Custom-made PLGA NPs were functionalized with an apolipoprotein E modified peptide (pep-apoE) responsible for LDLR binding, or with lipocalin-type prostagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Discovering new methods to treat diseases is becoming increasingly complicated because of the numerous natural biological barriers in our bodies such as opsonization by proteins in the blood, first-pass clearance organs, and the immune response [1,2]. The difficulty of overcoming these barriers to create a cure is exponentially increased when trying to deliver pharmaceutics across the blood-brain barrier (BBB) [3,4]. This is due to the brains increased security including tight junctions, low molecule diffusion rates, efflux transporters, and difficulty in reaching sufficient drug exposure in the brain compartment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Discovering new methods to treat diseases is becoming increasingly complicated because of the numerous natural biological barriers in our bodies such as opsonization by proteins in the blood, first-pass clearance organs, and the immune response [1,2]. The difficulty of overcoming these barriers to create a cure is exponentially increased when trying to deliver pharmaceutics across the blood-brain barrier (BBB) [3,4]. This is due to the brains increased security including tight junctions, low molecule diffusion rates, efflux transporters, and difficulty in reaching sufficient drug exposure in the brain compartment [5].…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles are functionalized through covalent linkage to bind with recombinant L-PGDS which has an affinity to the aggregated amyloids in AD brain. Binding of the L-PGDS to the nanoparticles can indeed enhance their assimilation into the brain regions [18] [19][20][21]. A general protocol for the preparation of stable iron oxide nanoparticles involving the decomposition of the iron-oleate complex at high temperatures is reported elsewhere [22].…”
Section: Resultsmentioning
confidence: 99%
“…Its key role in the sleepwake cycle, differential expression in neuronal cells, upregulation in neurological disorders, and interactions with the receptors in the brain make it an ideal candidate for the AD probe design [36][37][38][39]. Furthermore, L-PGDS has been previously used to transport small lipophilic drugs into the brain and formulated in brain medications to enhance their targeting across the BBB [18,40]. We showed that L-PGDS is capable of binding more than 20 proteins from the insoluble aggregates in human AD brain [4].…”
Section: Discussionmentioning
confidence: 99%
“…They show tremendous potential as diagnostic and therapeutic tools for MRI in AD brains. L-PGDS can bind to the low-density lipoprotein receptor in the brain, which facilitates the transport of conjugated nanoparticles for brain targeting across the BBB [38]. The ability of L-PGDS to bind and disassemble Aβ at sub-stoichiometric concentrations renders an added advantage to its development as a non-invasive intranasally administered tracer.…”
Section: Magnetic Resonance Imaging Probes For Alzheimer's Disease Thmentioning
confidence: 99%